2019
DOI: 10.1108/sajbs-08-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility investment, third-party assurance and firm performance in India

Abstract: Purpose Corporate social responsibility (CSR) has evolved since the nineteenth century and is becoming mandatory for firms. However, the association between CSR and financial performance remains fluid. The purpose of this paper is to examine the mediating effect of third-party assurance (TPA) and the moderating effect of financial leverage in CSR – financial performance relationship. Design/methodology/approach Panel and hierarchical regression models are used to analyse data covering 29 companies in the Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 93 publications
4
28
0
2
Order By: Relevance
“…The results showed that corporate social responsibility has a positive and significant effect on brand performance. This finding is consistent with Selcuk and Kiymaz [11], Rahman and Yu [12], Lin et al [13], Oware and Mallikarjunappa [14], Kong et al [15] and Naseem et al [16]. To explain this finding, it can be claimed that brand performance will be improved if the company supports employee higher education, encourages employees to develop their skills and abilities, implements flexible policies to provide work-life balance for employees, prioritizes employee needs and demands, provides accurate and comprehensive information to customers, cares about customer rights and satisfaction beyond legal requirements, has plans to reduce the negative effects of the company on the environment, and participates in activities aimed at protecting and improving the quality of the environment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that corporate social responsibility has a positive and significant effect on brand performance. This finding is consistent with Selcuk and Kiymaz [11], Rahman and Yu [12], Lin et al [13], Oware and Mallikarjunappa [14], Kong et al [15] and Naseem et al [16]. To explain this finding, it can be claimed that brand performance will be improved if the company supports employee higher education, encourages employees to develop their skills and abilities, implements flexible policies to provide work-life balance for employees, prioritizes employee needs and demands, provides accurate and comprehensive information to customers, cares about customer rights and satisfaction beyond legal requirements, has plans to reduce the negative effects of the company on the environment, and participates in activities aimed at protecting and improving the quality of the environment.…”
Section: Discussionsupporting
confidence: 89%
“…Although the main goal of organizations is to increase efficiency and profit, in the age of information and globalization, they must respond appropriately to social expectations and ethical norms to achieve success, and best combine such expectations with economic goals of the organization to enable the achievement of higher goals. Studies that have examined the relationship between corporate social responsibility and corporate performance have shown that there is a positive and significant relationship between corporate social responsibility and corporate performance [11][12][13][14][15][16]. Therefore, it is assumed: Hypothesis 1: Corporate social responsibility has a positive and significant effect on brand performance.…”
Section: Introductionmentioning
confidence: 99%
“…The social responsibility and sustainability report were conducted as an effort by the company to discover and understand its current and long-term targets. This statement follows a study by Oware and Mallikarjunappa [17], as well as by Bhernadha et al, [18]. These studies result proved that the sustainability report significantly affected financial performance.…”
Section: Research Hypothesessupporting
confidence: 90%
“…They found that CSR disclosure has a positive and significant effect on corporate survival. Oware and Mallikarjunappa (2019) show a positive and significant association between CSR performance and FP. Many studies find a positive relationship between CSR and FP (Nollet et al , 2016; Freeman and Dmytriyev, 2017; Maqbool and Bakr, 2019; Partalidou et al , 2020).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 83%